Filogenia de Acentroscelus Simon, 1886 (Araneae: Thomisidae) e a evolução do nanismo nas aranhas caranguejo - Molina Gómez, Diana Paola (2020)
Acentroscelus is a genus of neotropical spiders belonging to the Tmarini tribe and characterized by its small size. Currently, knowledge of this genus is limited to the original taxonomic descriptions of its species. In order to test the evolutionary relations of the genus and to unravel the taxonomic classification of its species, we performed a phylogenetic analysis, the taxonomic revision of the group, and through the use of morphometric tools we made integrative notes on two species of Acentroscelus. For this, our work has been divided into three main phases. The first phase corresponds to the taxonomic validation of Acentroscelus ramboi and Acentroscelus versicolor, whose descriptions were originally made based on the morphology of females and their males present a high morphological similarity. Assessing the carapace and pedipalp of males of these two species, we obtained a clear disparity. With the results of the test made from the use of anatomical landmarks we ratified the taxonomic validity, finding that besides the clear difference of the females, the males of A. ramboi have the prosoma wider and flatter than the males of A. versicolor; besides presenting the ventral apophysis of the tibia (VTA) thinner at the base and its ectal branch more curved. The second phase corresponds to the phylogenetic analysis based on morphological characters. In this test we confirmed the monophily of the evaluated group, but we found the clade subdivided into three groups. Based on these clates, we proposed the subdivision of Acentroscelus latu sensu into three different genera: Maeanderion, Whittickius and Acentroscelus. In addition to the first systematic approach of the group, we evaluated the body size in the Tmarini species included in the analysis, describing the clado Acentroscelus latu sensu as spiders in miniaturization condition. Finally, the third phase was the taxonomic revision of Acentroscelus latu sensu. We diagnosed and described Maeanderion, with Maeanderion peruvianus (Keyserling, 1880) as the only species of the genus. Besides, we revalidated the Amazonian genus Whittickius (Mello-Leitão, 1940) with W. singularis (Mello-Leitão, 1940) as a type species; we redescribed inside this genus W. granulosus and W. guianensis, whose male was described for the first time; and we described two new species: W. caxiuana and W.echinithorax. Acentroscelus stricto sensu was re described together with its five species, distributed in the Atlantic Forest: Acentroscelus albipes, Acentroscelus versicolor, Acentroscelus ramboi and two new species. Acentroscelus muricatus has been considered as junior synonym of the species type A. albipes.